Changes in the hydrometeorological conditions for sustainable water resources planning and management framework in Ethiopia - Sahoo, Satiprasad; Govind, Ajit (CGIAR FOCUS Climate Security, 2022)
Ethiopia’s agriculture sector is largely rainfed and thus more vulnerable to climate change. Water resource management is critical for enhancing climate resilience in Ethiopian agriculture. In this study, we analyzed the spatiotemporal trend of historical climatic data in Ethiopia at the sub-regional level. We also analyzed the spatiotemporal trends of historical hydrological parameters for sustainable and efficient use of water resources in the era of climate uncertainty. We developed a framework for terrestrial water storage and groundwater storage mapping for the variability of the dryness and wetness conditions using the Global Land Data Assimilation System (GLDAS) and Gravity Recovery and Climate Experiment (GRACE) data.